Partisipasi Masyarakat Dalam Pengelolaan Taman Wisata Alam Gunung Meja Di Kabupaten Manokwari (Studi Kasus Kampung Ayambori) - Altar Sawaki; Ludia T. Wambrauw; Anton S. Sinery (Cassowary, 2019)
The aim of the research is to know the participation degree of local communities in the management program of Gunung Meja natural recreation park and contribute alternative recomendations for his management based on community the participation. The results of the research, are that community participation in management of Gunung Meja natural recreation park is highest for family group (46,15%) and the lowest is for the leader group (5,13%). The same case also find in community partisipation intensity. The participation of community include leaders, interests, household head, housewife and youth with categorise as very inactive. This inactive result is influenced by community participation function which is in general only participate on activity implemention and share informations as well as consultation. The management efforts are permit of natural tourism utilysation and natural resources tourism infrastructure utilizatio, that can be used as the base of management program.